Fibrine rich in platelets (Research, Society and Development, 2021)
Until recently, postoperative periods, both in medicine and dentistry, were considered factors that prevented some patients from performing the necessary procedures. With technological and scientific advancement, it was possible to develop platelet concentrates that assist in the postoperative period, since, when used, they help to accelerate the healing and tissue regeneration processes, which reduces the discomfort time of the postoperative period. The first platelet concentrate was Plasma Rich in Platelets; this, in turn, is considered a first generation platelet concentrate that, due to certain limitations, ended up making professionals stop using it. It was only in 2001 that the second generation platelet concentrate, also known as Fibrin Rich in Platelets, was introduced to the world, which had several advantages over the first generation platelet concentrates and, since then, has received several modifications, which have given rise to other varieties of it , which have been widely used until today, together with the original Fibrin Rich in Platelets. The present work aims to carry out, in a didactic way, an aggregate of information about the PRF, in order to present it to the dental community. At the end of this study, it was concluded that the PRF was a major milestone for Dentistry, generating security for the professional and for the patient. Articles obtained through the online platforms: VHL, Pubmed and Lilacs were used as bibliographic bases. With this, after the analysis and absorption of the material used as a reference, this work was written.